Prophylaxis and treatment of nosocomial infections in patients under short-term mechanical circulatory support. (3rd May 2023) - Alonso Fernandez De Gatta, M; Hernandez Martos, A V; Esteban Milla, L; Martin Herrero, F; Moreta Matilla, M; Diego Nieto, A; Merchan Gomez, S; Gonzalez Cebrian, M; Toranzo Nieto, I; Barrio Rodriguez, A; Cid Menendez, A; Gonzalez Calle, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Infections are frequent in patients requiring short-term mechanical circulatory support (MCS). The definition and diagnosis of infection is complex and variable, antibiotic prophylaxis is not clearly recommended, and treatment is not established. Purpose: Our objective was to describe the profile of infections in patients with short-term MCS, as well as review local experience in antimicrobial prophylaxis and therapeutics and their relation to infection appearance and their prognostic influence. Methods: Retrospective analysis of consecutive cases of venoarterial extracorporeal membrane oxygenator (VA-ECMO) or Impella CP® implantation in a referral center. We characterized the infections and antimicrobial treatment received during hospitalization. We define infection as microbiological isolation (no colonization) or clinical suspicion that motivates antimicrobial therapy with therapeutic intent. Results: 232 patients were included between 2014-sep 2022 (Table). A total of 104 (56.5%) patients presented infection during the admission, being respiratory tract (other than pneumonia) (23.3%) was the most prevalent (figure-A). Positive cultures were obtained in 28.4% of the patients, staphylococcus spp and gram-negative bacilli the most frequently isolated germs (figure-B). 28.1% of the cases were suspected infections without microbiological isolation. Infection appeared during MCS in 25% of patients, 13% after its removal, 11% at both times (different infections), and 6.1% of patients were already infected at MCS implant. 65.1% of patients received antibiotic prophylaxis for the implantation (figure-C) during a median of 2 [3] days. It was used more frequently with the VA-ECMO (74.9%) than Impella CP device (48.5%) (p<0.001) as well as in urgent MCS indications different than elective high-risk percutaneous coronary intervention (p<0.001). The antimicrobials used (sometimes in combination) are summarized in figure-D. Overall in-hospital mortality was 59.8% (n=137), 3.9% due to infection. No direct relationship was observed between in-hospital mortality and the presence of infection (57.4% in infected patients vs 61.7% without infection, p=0.587). Patients who received antibiotic prophylaxis had a higher frequency of infection during admission (53.6% infection with prophylaxis vs 25.6% infection without prophylaxis, p<0.001), and suffered lower hospital survival (32.9% survival with prophylaxis vs 53.8% without, p=0.009). The use of antimicrobial treatment with therapeutic intent did not influence survival (40.1% survival with antimicrobials vs 39.3% without, p=0.643). Conclusions: Nosocomial infections in patients requiring short-term MCS (VA-ECMO or Impella) are frequent but in our population infection was not associated with higher hospital mortality. Antibiotic prophylaxis does not seem to prevent the development of infections nor is associated with increased survival. Further randomized studies are needed to establish recommendations.